Oxidative Processes and Xenobiotic Metabolism in Plants: Mechanisms of Defense and Potential Therapeutic Implications - Caterina Vicidomini; Rosanna Palumbo; Maria Moccia; Giovanni N. Roviello (Journal of Xenobiotics)
Plants are continuously exposed to environmental challenges, including pollutants, pesticides, and heavy metals, collectively termed xenobiotics. These substances induce oxidative stress by generating reactive oxygen species (ROS), which can damage cellular components such as lipids, proteins, and nucleic acids. To counteract this, plants have evolved complex metabolic pathways to detoxify and process these harmful compounds. Oxidative stress in plants primarily arises from the overproduction of hydrogen peroxide (H2O2), superoxide anions (O2•−), singlet oxygen (1O2), and hydroxyl radicals (•OH), by-products of metabolic activities such as photosynthesis and respiration. The presence of xenobiotics leads to a notable increase in ROS, which can result in cellular damage and metabolic disruption. To combat this, plants have developed a strong antioxidant defense mechanism that includes enzymatic antioxidants that work together to eliminate ROS, thereby reducing their harmful effects. In addition to enzymatic defenses, plants also synthesize various non-enzymatic antioxidants, including flavonoids, phenolic acids, and vitamins. These compounds effectively neutralize ROS and help regenerate other antioxidants, offering extensive protection against oxidative stress. The metabolism of xenobiotic substances in plants occurs in three stages: the first involves modification, which refers to the chemical alteration of xenobiotics to make them less harmful. The second involves conjugation, where the modified xenobiotics are combined with other substances to increase their solubility, facilitating their elimination from the plant. The third stage involves compartmentalization, which is the storage or isolation of conjugated xenobiotics in specific parts of the plant, helping to prevent damage to vital cellular functions. Secondary metabolites found in plants, such as alkaloids, terpenoids, and flavonoids, play a vital role in detoxification and the defense against oxidative stress. Gaining a deeper understanding of the oxidative mechanisms and the pathways of xenobiotic metabolism in plants is essential, as this knowledge can lead to the formulation of plant-derived strategies aimed at alleviating the effects of environmental pollution and enhancing human health by improving detoxification and antioxidant capabilities, as discussed in this review.